A Human-centered innovation process (HCIP) for evidence-based substance use prevention intervention implementation - Anthony Coetzer-Liversage; L.A.R Stein; Peggy C Stephens; Eric Jefferis; Mary Step; Alicia Crowe; Zili Sloboda (New Prairie Press, 2024)
Despite efforts in Implementation Science, there remains a considerable gap between establishing intervention effectiveness and their widespread adoption in real-world settings. Shockingly, only about 14% of these interventions make it into practice. This study recognized the urgent need for a paradigm shift within the field and sought to develop a comprehensive understanding of the systemic barriers and facilitators affecting intervention implementation. To achieve this goal, a qualitative methodology known as constructivist grounded theory was employed. This approach allowed for the exploration of rich, in-depth descriptions and theoretical insights derived from the experiences of 30 prevention professionals who have been involved in implementing evidence-based interventions for substance use prevention. Data collection involved various methods, including semi-structured interviews, elicited descriptions of lived experiences, participant documents, and analysis of existing literature. Through systematic analysis, the study constructed a central process characterized as a human-centered innovating process. This process was found to be cyclical, nonsequential, and iterative, involving overlapping stages of engagement, collaboration, negotiation, iteration, and implementation. These findings shed light on the complexities inherent in implementing evidence-based interventions and provide valuable insights for researchers and practitioners alike. Ultimately, this grounded theory offers a substantive approach to understanding evidence-based intervention implementation as an innovation process. By highlighting the importance of human-centered approaches and iterative strategies, it provides a roadmap for optimizing the translation of evidence-based interventions into real-world practice.